Community action: value or instrument? An ethics and planning critical review - Tricarico, Luca (Journal of Architecture and Urbanism, 2017)
The community concept has maintained a constant and growing interest in urban studies and many related fields. The origin of this continuing interest seems to derive from the importance of the concept of community within diverse forms of political language and interpretations within different planning practices. In this contribution, through the analysis of different ethical and planning theories, we want to provide an update framework on community action. According to this objective, the argumentation will proceed through a literature review on four ethics theories and three key aspects related to spatial planning, as well as matching this theoretical analysis with exemplifying practices. The final objective is to provide an original analysis on drivers and outcomes of different forms of community, raising general issues that refer to spatial planning, social organization and regulation.